Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques